Form and Genre Access to Academic Library Digital Collections - Dragon, Patricia M. (My University, 2020)
This paper provides an examination of how digital collections in academic libraries provide user access to items by form and/or genre. A review of the literature reveals that this is not an area that has received much attention, despite an increased focus on digital collections metadata and on the user experience, as well as the development of form/genre vocabularies on the national scale, such as the Library of Congress Genre/Form Terms (LCGFT). Over 100 North American digital collections websites were examined, and the results blended with data received from communications with parties responsible for digital collections metadata. The goals were to reveal possibilities for improving East Carolina University’s digital collections website, and additionally to stimulate discussion in the metadata community about best practices in form/genre access for library digital collections.
The Version of Record of this manuscript has been published and is available in Journal of Library Metadata, 17 Feb. 2020, DOI: 10.1080/19386389.2020.1723203.
Keywords: Genres; Forms; Dublin Core; Digital collections; User interface